Pain and its management: a precise summary - Ghosh, Debadrita; Mukherjee, Chitrita Gupta; Kumar, Arvind (International Journal of Research in Medical Sciences, 2026)
Pain may be portrayed as an unpleasant, subjective, sensation, that may be resulting from a sudden ‘tissue damage’. ‘Pain management’; implemented for patients should involve both ‘pharmacologic’ and ‘nonpharmacologic’ protocols. Medical therapies, such as mind-body practice, acupuncture, massage therapy, and music therapy, have been well appreciated for their roles in pain management. Since recent past, numerous studies have emphasized upon the effect of hypnosis, acupuncture, and music therapy in reduction of pain. Mindfulness meditation, yoga, qigong, and massage therapy, although may not bear the potential of completely reducing the pain, but can still offer adequate relief from persistent anxiety and phenomenal mood changes, which may be commonly associated with pain. Recent screening tools and brief intervention techniques can be effective in helping clinicians identify, stratify and manage both patients already living with chronic pain and those who are at risk of developing chronic pain from acute pain. Frequent assessment and re-assessment are key to ensuring treatment is appropriate and safe, as well as minimizing and addressing side effects. Therefore, in clinical practice, it is always suggested for the practitioners; to earnestly consider the various burdens and risks to patients, consequent patient preference, and the presence or absence of better alternatives while opting for an integrative medical therapy.